E(in)volution of standards in student housing design - Claudio Piferi (Techne)
Calls for tenders published since 2001 under Law no. 338/00 have been characterised over the years by a gradual reduction in the standards and functional areas prescribed. This contraction, strongly accentuated by the decrees recently issued to reach 7,500 accommodation places by 2022 and 60,000 by 2026, risks undermining the virtuousness of the law by focusing primarily on economic and managerial aspects rather than on the quality of student housing and education. By collecting and processing unique data in terms of number and originality, this paper analyses and systematises the e(in)volution of the legal framework by comparing it with over 350 projects and constructions of university residences co-financed under the above-mentioned calls.